Equiconvergence in summation associated with elliptic polynomial - Fargana, A; Rakhimov, Abdumalik; Khan, Ahsan Ali; Hassan, Torla (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
In this paper we prove a precise equiconvergence relation between index of the Bochner-Riesz means of the expansions and power of the singularity of the distributions with compact support in summation associated with the elliptic operator.